Application and Energy-saving Analysis of Built-in Array Acoustic Sootblower - Lei ZHOU; Ju ZHANG; Ziyuan SONG; Zhiping YANG; Peihu GUO; Haiping XIAO; Chen ZHANG; Jianlong LI (发电技术)
Because the traditional steam sootblowing technology has a dead corner, it needs a lot of high quality steam, and the safety of the steam is affected by the scouring of the heating surface. Therefore, in recent years, many new power plants tend to adopt built-in array acoustic sootblower in the low-temperature flue to purge the low-temperature reheater, low-temperature superheater and economizer. Combined with the application of acoustic sootblower in a 660 MW power plant, the economic evaluation was studied. The sootblowing economy was evaluated by two indexes:boiler efficiency at boiler side and steam turbine thermal efficiency at turbine side. The boiler anti-balance method was used to calculate the boiler efficiency variation when the exhaust gas temperature changed 1℃ under a certain load. The increase of boiler efficiency was calculated by the decrease of flue gas temperature after sootblowing, and the decrease of coal consumption was further calculated. By using the calculation method of heat carrying out system by working medium in the equivalent enthalpy drop method, the influence of sootblowing steam on the heat consumption of steam turbine was obtained, and the increase of coal consumption was further calculated. The economic gain of acoustic sootblower was obtained by considering the economic evaluation of boiler side and steam turbine side. The results show that compared with the conventional steam sootblower, the annual cost saving of the built-in array acoustic sootblower is more than 1 million yuan. In addition, it will have better energy-saving effect for units with poor economic performance for many years.